Assessment of nasal septum after Le Fort I osteotomy with computer tomography. Issue 9 (September 2016) - Moroi, Akinori; Yoshizawa, Kunio; Tsutsui, Takamitsu; Saida, Yuriko; Hotta, Asami; Fukaya, Kenichi; Hiraide, Ryota; Takayama, Akihiro; Tunoda, Tatsuya; Saito, Yuuki; Ueki, Koichiro
Abstract: The purpose of this study was to evaluate the effects of Le Fort I osteotomy on nasal septum deviation and differences in left and right airway sizes, and to determine whether the nasal septum was affected by differences in the direction of movement. Forty patients underwent conventional Le Fort I osteotomy, and computed tomography (CT) was performed preoperatively, and 1 week and 1 year postoperatively. The nasal septum angle and airway area were measured at the anterior, middle, and posterior positions on the CT images Patients were divided into 2 groups depending on each difference in movement (impaction ≥5 mm or other; anterior movement or other; and impaction asymmetry or other). There were no significant differences in the nasal septum angle and the airway of all patients. Among the patient groups, there were no significant differences in the nasal septum angle and airway. We concluded that conventional LI osteotomy did not influence the nasal septum deviation or the left and right airway asymmetry. Differences in the method of moving the maxilla have not been shown to affect changes in the nasal septum.